2019
DOI: 10.1016/j.knee.2018.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Preservation vs. resection of the infrapatellar fat pad during total knee arthroplasty Part I: A survey of current practice in the UK

Abstract: This is a repository copy of Preservation vs. resection of the infrapatellar fat pad during total knee arthroplasty Part I: A survey of current practice in the UK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…These results are similar to the 2004 UK and Wales National Joint Registry report [19]. Similarly, in a survey of orthopedic surgeons in England conducted by van Duren et al [20] (n=173), 9.83% of the respondents stated that they completely preserve the IPFP. In addition, only 23%…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These results are similar to the 2004 UK and Wales National Joint Registry report [19]. Similarly, in a survey of orthopedic surgeons in England conducted by van Duren et al [20] (n=173), 9.83% of the respondents stated that they completely preserve the IPFP. In addition, only 23%…”
Section: Discussionsupporting
confidence: 87%
“…In a survey of 173 orthopedic surgeons in the UK, 9.83% of respondents preferred total preservation of the IPFP, 23.12% preferred total resection, and 62.4% favored partial resection. Furthermore, only 23% of respondents were aware of any guidelines or evidence to support their surgical decision [20].…”
Section: Discussionmentioning
confidence: 99%
“…Awareness about IFP role is extremely important also in clinical practice. In fact, IFP preservation or resection during TKA is still a matter of debate and no definitive guidelines are available [37]. Even though IFP resection during knee surgery allows easy access and visualization, evidence suggests that its preservation is advantageous [38].…”
Section: The Role Of the Ifp-synovial Membrane As A Functional Unimentioning
confidence: 99%
“…Several studies demonstrated that IFP excision is associated with increased anterior knee pain: Macule et al reported increased pain 6 months following TKA, while in a study by Nisar et al elevated pain was observed at 1-2 months post-op [14,30]. Pinsornask et al demonstrated comparable pain intensity at 2 months, but increased pain in knees with IFP resection at 12 months; other authors also indicated anterior knee pain associated with Hoffa fat pad resection at follow-ups longer than 6 months [7,20,31].…”
Section: Discussionmentioning
confidence: 99%